Bad English : literature, multilingualism, and the politics of language in contemporary Britain - Gilmour, Rachael, 1973- (Manchester University Press Ser., 2020)
Bad English examines the impact of increasing language diversity in transforming contemporary literature in Britain, in the context of its contested language politics. Exploring a range of poetry and prose, it makes the case for literature as the preeminent medium to probe the terms and conditions of linguistic belonging.